Could the pulp be preserved in tooth with root resorption caused by embedded tooth? - Yuxue Luo; Tao Qu; Jingyuan Huang; Chang Liu; Yubin Cao; Chengge Hua (Elsevier, 2023)
Background/purpose: At present, there are no recognized guidelines or consensus for the treatment strategy of the asymptomatic tooth with external root resorption caused by an embedded tooth (et-ERR). Most clinicians would like prophylactic or concomitant root canal therapy (RCT) along with the extraction of the embedded tooth. The purpose of this study was to report the prognosis of external root resorption (ERR) and investigate the possibility to preserve the vital pulp of ERR tooth. Materials and methods: The patients who had asymptomatic et-ERR teeth were included. After extraction of the embedded tooth, the clinical process, prognosis, and adverse events were observed, including symptoms, clinical, and radiographic examination throughout the follow-up period. Results: A total of four cases with special features were reported. Over a follow-up period of up to 12 months, on clinical examination, 3 ERR teeth preserved pulp vitality without additional intervention except for tooth extraction and have kept normal function free from any symptoms. Radiographic examination showed bone regeneration and recovery of periodontal tissue. While one case failed to keep the vital pulp and ended in intentional replantation. Conclusion: As to et-ERR, if the embedded tooth can be promptly extracted with a minimally invasive technique and effective infection control, the pulp vitality of the et-ERR tooth is likely to be preserved. In this situation, the preferred management of asymptomatic et-ERR tooth is just followed up without prophylactic RCT.